2009
DOI: 10.5194/angeo-27-4533-2009
|View full text |Cite
|
Sign up to set email alerts
|

Rosetta and Mars Express observations of the influence of high solar wind pressure on the Martian plasma environment

Abstract: Abstract. We report on new simultaneous in-situ observations at Mars from Rosetta and Mars Express (MEX) on how the Martian plasma environment is affected by high pressure solar wind. A significant sharp increase in solar wind density, magnetic field strength and turbulence followed by a gradual increase in solar wind velocity is observed during ∼24 h in the combined data set from both spacecraft after Rosetta's closest approach to Mars on 25 February 2007. The bow shock and magnetic pileup boundary are coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
(46 reference statements)
4
25
0
Order By: Relevance
“…[], and in two event studies for CIR‐related solar wind disturbances by Edberg et al . [] and Dubinin et al . [].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[], and in two event studies for CIR‐related solar wind disturbances by Edberg et al . [] and Dubinin et al . [].…”
Section: Discussionmentioning
confidence: 99%
“…[], but it is different from the along‐terminator periapsis orbit geometry at the time of the Rosetta Mars flyby studied by Edberg et al . [].…”
Section: Campaign Overview and Instrumentationmentioning
confidence: 99%
“…When available, studies use in situ measurements, but these can be limited in instrument (e.g., no magnetometer on Mars Express) or continuity (e.g., orbits that spend little or no time in the upstream solar wind). When direct measurements are not available, studies have utilized solar wind proxies [e.g., Crider et al ., ; Brain et al ., ], spacecraft flybys near Mars [e.g., Edberg et al ., ], and/or 1 AU in situ conditions when Earth and Mars share Parker spiral alignment [e.g., Vennerstrom et al ., ; Dubinin et al ., ; Edberg et al ., ; Opgenoorth et al ., ]. Despite the variety of techniques used to determine upstream solar wind conditions, modeling the solar wind at Mars' orbital location from initial solar conditions has only rarely been used [e.g., Jakosky et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Edberg et al [] used Rosetta observations to provide the solar wind conditions in the vicinity of Mars to conclusively show that energetic (100 eV–10 keV) planetary ions were escaping in the + E SW direction. The study showed two MEX orbits with energetic planetary ions beyond the IMB, flowing away from Mars in the + E SW direction.…”
Section: Introductionmentioning
confidence: 99%